Development of guidance for the adoption of circular economy in construction and demolition waste management - Salleh, Hafez; Chow, Ke Ying; Hanid, Mahanim; Abdul Samad, Zulkiflee; Mohamed Sabli, Nor Azlinda; Syed Khuzzan Alhabshi, Sh Mazlina (Malaysian Institute of Planners, 2022)
The rise in the amount of construction and demolition waste and its negative impacts on the environment had made it become a hot issue globally. Therefore, efficient construction and demolition waste management are extremely important in the construction industry. The circular economy is introduced to shift the current linear economy practice of “take-make-consume-dispose” to “take-makeconsume-reuse and recycle” toward a more sustainable and efficient construction and demolition waste management by decrease the illegal dumping and construction and demolition waste issues. However, the concept of circular economy has still not been widely developed in current practices of waste management where many of the players in the construction industry still in the process of understanding how to adopt circular economy practices. Thus, this research aims to develop the strategy for the adoption of Circular Economy (CE) for Construction and Demolition Waste Management (CDWM). The quantitative method is applied in this research to collect data and the data is collected through a questionnaire survey. A strategy is proposed on the adoption of the circular economy principle in the construction and demolition waste sector as a reference to improve the performance of the current construction and demolition waste management system.